Peran Strategi Pemasaran Digital dan Kualitas Produk dalam Meningkatkan Loyalitas Pelanggan Produk Emping Melinjo pada Merek Snack Crunchy Ku Kecamatan Cikedal Kabupaten Pandeglang - Afifah, Rizka Mauliani; Wandi, Didi; Azizi, Enji (INDO PUBLISHING, 2026)
This study aims to explore the role of digital marketing strategies and product quality in enhancing customer loyalty toward the Snack Crunchy Ku melinjo chips brand in Cikedal District, Pandeglang Regency. The research adopts a descriptive qualitative approach, utilizing in-depth interviews, observations, and documentation involving business owners, employees, and loyal customers. The findings reveal that digital marketing strategies through social media platforms such as Instagram and WhatsApp Business are effective in reaching consumers and establishing two-way communication. Meanwhile, product quality—encompassing taste, crispiness, packaging, and hygiene plays a vital role in creating customer satisfaction and fostering loyalty. These two factors are interrelated and contribute to customer loyalty, as reflected in repeat purchases and product recommendations to others. This research provides recommendations for MSMEs to consistently integrate digital marketing strategies with continuous product quality improvement to strengthen their competitiveness in the market.